2022
DOI: 10.1021/acsanm.2c02524
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Ligand-Capped Plasmonic Au Nanoparticle Films in the Kretschmann Configuration for Sensing of Volatile Organic Compounds

Abstract: fabrication methods for volatile organic compound (VOC) sensing applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…When plasmonic nanostructures are arranged periodically, electrodynamic coupling of the nanostructures enhances the light-matter interaction as compared to isolated nanostructures 1 , 2 . Thus, periodic arrays of nanostructures have gained increasing attention in recent years for the application in light driven processes such as solar energy harvesting 3 , photovoltaics 4 , photocatalysis 5 , 6 , SERS (surface-enhanced Raman spectroscopy) 7 , fluorescence 8 , SEIRA (surface-enhanced infrared absorption spectroscopy) 9 , sensing 10 , photoemission and photodetection 11 , etc. The plasmonic enhancement of these various processes can occur through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…When plasmonic nanostructures are arranged periodically, electrodynamic coupling of the nanostructures enhances the light-matter interaction as compared to isolated nanostructures 1 , 2 . Thus, periodic arrays of nanostructures have gained increasing attention in recent years for the application in light driven processes such as solar energy harvesting 3 , photovoltaics 4 , photocatalysis 5 , 6 , SERS (surface-enhanced Raman spectroscopy) 7 , fluorescence 8 , SEIRA (surface-enhanced infrared absorption spectroscopy) 9 , sensing 10 , photoemission and photodetection 11 , etc. The plasmonic enhancement of these various processes can occur through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[183] [184] For example, among different VOCs, certain aldehydes in breath have been identified as biomarkers of lung cancer [185] The combination of MOFs with self-assembled plasmonic nanoparticles facilitates high absorption of the probe molecules in the porous MOF, where their SERS intensity is amplified by the strong nearfield enhancement of coupled plasmonic response of the nanoparticles, Figure 15 (e). Recently, Borah et al [186] have shown an alternative strategy for the detection of VOCs by self-assembled Au nanoparticle films in the Kretschmann (i.e. Attenuated Total Reflection, ATR) configuration, where the adsorbed VOCs on the nanoparticles can be detected by the change in the optical intensities due to the change in refractive index, Figure 15 (f).…”
Section: 14mentioning
confidence: 99%
“…It is shown that further improvement in sensitivity can be achieved by the use of ellipsometry instead of intensity based optical spectroscopy. [186] Refractive index based sensing by plasmonic nanostructures is based on the change in the optical intensities or plasmon resonance positions (usually a red shift) due to the change in the refractive index in the surrounding medium of the nanoparticles after interaction with the analyte. Naturally, the adsorption of biomolecules (in liquid phase), gases, VOCs, etc., on the plasmonic nanostructure leads to this change in the refractive index.…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation
“…The peak and width values of the SPR absorption spectra are very sensitive to the variation of the sensing layer refractive index. As a result, this configuration can determine the chemical bonds formed between the molecules (for example, biomolecules BioMs) and the sensor (AgNPs). …”
Section: Introductionmentioning
confidence: 99%